E03 Longitudinal brain volume and glucose metabolism changes in patients with juvenile-onset Huntington disease. (12th September 2022) - Tinelli, Emanuele; Caligiuri, Maria Eugenia; Cicone, Francesco; Cascini, Giuseppe Lucio; Oliveti, Cesare; Colafati, Giovanna Stefania; Napolitano, Antonio; Maffi, Sabrina; Migliore, Simone; Scaricamazza, Eugenia; Quattrone, Aldo; Squitieri, Ferdinando; et al.
Abstract : Background: Many studies separately described volumetric and metabolic brain changes in Huntington disease (HD). No analysis has been so far performed on juvenile-onset HD (JOHD) by using hybrid instruments combining both brain morphometry and glucose uptake. Aim: To evaluate longitudinal brain volumetric and metabolic changes in patients with JOHD. Methods: We acquired simultaneous 3D-T1 and PET-FDG scans in two JOHD patients at 2 time-points. Structural and metabolic data were used to assess annualized changes in total brain and deep gray matter volume (caudate, putamen, thalami nuclei), in cortical thickness, as well as the corresponding changes in regional FDG-uptakes. Results: Both patients showed similar decrease in total brain volume, while a subject-specific pattern was observed in deep gray structures and cortical FDG-uptake changes. In patient 1, there was a symmetric decrease of subcortical and occipital volumes and FDG-uptakes, while fronto-parietal cortical regions showed an increase of FDG-uptakes paralleled by cortical thickness decrease. Patient 2, instead, showed greater structural and metabolic damage in the left hemisphere, especially involving caudate, with an increase of right cortical FDG-uptake particularly evident in fronto-parietal regions. Conclusion: Hybrid PET/MRI is a useful advanced technique to individually characterize neurodegenerative processes underlying JOHD. These processes seem to be more severe in JOHD than in adulthood-HD, in terms of yearly structural and metabolic changes. Our study suggests that JOHD evolves with variable volume loss across brain regions, along with variable compensatory effects of cortical glucose metabolism, advising tailored assessments for monitoring disease progression and therapeutic efficacy.